Experimental and Modelling Analysis of Liquid-Liquid Formation in Alcohol-mixed Gasoline Fuel - Patthranit Wongpromrat; Muntira Rukquan; Amata Anantpinijwatna (Chemical Engineering Transactions, 2019)
To tackle the environmental and sustainability problems, substituting gasoline, partially or solitary with bio-based alcohols becomes global practice. Bioethanol and biomethanol are being blended with gasoline in the ratio between 5-100 % by volume varying on the region. Various studies show positive impact of utilizing the blended fuel environmentally, while the others report the adequate efficiency of the blended fuel compare to the conventional gasoline; however, there were nearly no report on the failure or the shorten lifespan of the engine parts such as a high pressure pump (HPP) or an injector. It has been reported that water residue in the blended-bioethanol and biomethanol could cause the formation of the second liquid phase, leading to the chemical ageing reaction, which resulted in the corrosion of the HPP. To understand and prevent the damage, a quaternary behaviour of the blended gasoline-ethanol-methanol-water at the HPP operating condition is needed. In this work, an experimental study of the quaternary behaviour of the blended fuels has been conducted, the experimental data have been matching with the simulated results for better predictive of the mixture behaviour at different conditions. These results could potentially lead to limit or eliminate the HPP-corrosive problem.